1987
DOI: 10.1113/jphysiol.1987.sp016358
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of neurally mediated vasodilatation in hairy skin of the human foot.

Abstract: SUMMARY1. Intraneural stimulation (i.n.s.) was made in the superficial peroneal nerve at the ankle in seventeen healthy subjects. The effect on skin blood flow was monitored by laser-doppler flowmeters and photo-electrical pulse plethysmographs inside and outside the innervation zone of the stimulated nerve fascicle. I.n.s. was applied before and after proximal local anaesthesia of the stimulated nerve.2. Painful i.n.s. (stimulation strength 0-3-4 V) induced skin vasodilatation with the following characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 32 publications
(33 reference statements)
2
41
1
1
Order By: Relevance
“…This indicates that this response results from an increased level of afferent input from the loosely ligated sciatic nerve to the spinal cord. This finding agrees with the results of Blumberg and Wallin, 6 who also demonstrated that local anesthesia of a nerve proximal to its stimulation site completely interrupted the contralateral vasodilator response. Our findings also indicate that not only electrical, 6,32 but also other forms of excitation of nociceptive afferents (such as loose sciatic nerve ligation) may induce a vasodilator response in the contralateral extremity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This indicates that this response results from an increased level of afferent input from the loosely ligated sciatic nerve to the spinal cord. This finding agrees with the results of Blumberg and Wallin, 6 who also demonstrated that local anesthesia of a nerve proximal to its stimulation site completely interrupted the contralateral vasodilator response. Our findings also indicate that not only electrical, 6,32 but also other forms of excitation of nociceptive afferents (such as loose sciatic nerve ligation) may induce a vasodilator response in the contralateral extremity.…”
Section: Discussionsupporting
confidence: 83%
“…Blumberg and Wallin 6 have demonstrated that, in humans, painful intraneural electrical stimulation increases skin blood flow (SBF) not only ipsilaterally, but also in the contralateral extremity. Since the vasodilator response in the non-stimulated extremity occurred only when stimulation strength was high enough to cause sharp and localized pain, the authors proposed that the afferent limb of this reflex involves excitation of A-fibers.…”
mentioning
confidence: 99%
“…With increasing currents the flow sometimes decreased linearly (Fig. 6) (Blumberg & Wallin, 1987). Sympathetic outflow to the foot reaches the sympathetic chain through preganglionic fibres in the T9-L2 ventral roots (Normell, 1974).…”
Section: Changes Of Blood Flow In the Deep Femoral Arterymentioning
confidence: 99%
“…Together, these findings suggest that noxious stimulation of the upper limb evokes vasoconstriction in that limb, possibly due to a nociceptive-sympathetic vasoconstrictor spinal reflex. Painful intraneural stimulation of the superficial peroneal nerve evokes vasoconstriction in the palm of the hand (Blumberg & Wallin, 1987). Surprisingly, however, this stimulus also elicits reflex vasodilatation in both feet which is greater on the stimulated than opposite side (Blumberg & Wallin, 1987) (Drummond & Granston, 2003;Drummond & Granston, 2004;Drummond, 2006a) could be organized either at the spinal level or more rostrally.…”
Section: Resultsmentioning
confidence: 96%
“…Painful intraneural stimulation of the superficial peroneal nerve evokes vasoconstriction in the palm of the hand (Blumberg & Wallin, 1987). Surprisingly, however, this stimulus also elicits reflex vasodilatation in both feet which is greater on the stimulated than opposite side (Blumberg & Wallin, 1987) (Drummond & Granston, 2003;Drummond & Granston, 2004;Drummond, 2006a) could be organized either at the spinal level or more rostrally. To distinguish between these two possibilities in the present study, we determined whether noxious stimulation of the lower limb (which is innervated by lumbar and sacral afferents and thus does not directly cross paths with sympathetic outflow to the face) would also evoke signs of ipsilateral extracranial vasodilatation.…”
Section: Resultsmentioning
confidence: 96%